PERANAN PENDAMPING LOKAL DESA DALAM MENDORONG PARTISIPASI MASYARAKAT - Syakirin, Risko; Guanti, Wiwin; Nursyamsiah, Nursyamsiah (Supremasi Hukum: Jurnal Penelitian Hukum, 2024)
The lack of community participation in village planning and development is caused by the limited understanding of existing laws and regulations, as well as the low level of trust that the community has in the less transparent and accountable performance of the Village Government. Village facilitators, as professional support personnel, must be able to fulfill their roles in order to encourage and enhance community participation in village planning and development. This research employs an empirical juridical and empirical sociological approach, which involves studying a phenomenon and facts related to community behavior occurring in the field, and subsequently connecting them with legal regulations relevant to the research issues. To stimulate community participation, Village Facilitators provide guidance and reinforcement on the importance of community involvement in every stage of village development.